Analisis Faktor Ekonomi Yang Mempengaruhi Volume Ekspor Pada Saat Krisis Di Indonesia - Martha Hendrati, Ignatia; Dwi S., Yunita (Jurnal Riset Ekonomi dan Bisnis, 2009)
This study aims to analyze how many the economic factors that influence the development of Indonesia's export volume. Variables used in this research are investments (X1), U.S. Dollar Exchange Rate (X2), Export Price Index (X3) and Gross Domestic Product (X4), using secondary data during the period of 15 years ie from year 1993 to 2007. Secondary data obtained from the Central Bureau of Statistics (BPS) in East Java. From the results obtained by testing the hypothesis that the variables X1, X2, X3, and X4 has a significant (real) on the dependent variable is Volume Exports in Indonesia, this is indicated by the test F test = 8.723 greater than Ftable = 3.48. The analysis tool used is multiple linear regression using secondary data for 15 years.Keywords: Investment, Exchange Rate, Export Price Index, GDP